The Wali, the Woman, the Lion: Pesisir Performance and Chinese and Persianate Islam on Java - Kathy Foley (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2026)
This study examines the influence of Chinese and Persian Muslims on performance traditions in both coastal regions and the highlands of West Java, and explores how these traditions have served as enduring records of the long history of Islamic cultural hybridity in the Malay–Indonesian world. Employing a qualitative approach, the study uses historical-cultural analysis of textual sources, performative forms, and oral narratives. The data include stories of the Wali Songo, representations of Chinese female figures in the mythologies of Islamic kingdoms, genealogies of wayang golek, and the depiction of leonine figures within ritual settings and martial arts traditions. The findings demonstrate that interactions among Shiʿi communities, Sufi diasporas, Chinese networks, and Persian influences during the fifteenth and sixteenth centuries contributed significantly to shaping Javanese religious life and aesthetics, particularly through the medium of performance. Traces of exchange across trade routes, social communities, and religious networks have remained preserved within contemporary artistic expressions. Despite periodic pressures from fundamentalist currents seeking to narrow the public expression of Southeast Asian Islam, performance traditions continue to function as spaces for the preservation of plural memories and intercultural encounters.This article contributes to scholarship on Islam Nusantara, cultural history, and performance studies by positioning West Javanese performance traditions as a “living archive” that not only preserves but also reactivates complex histories of diaspora contact, mobility, and Islamic diversity in Indonesia.